Evaluasi Risiko Muskuloskeletal dengan Metode REBA dan Nordic Body Map pada Stasiun Packing Industri Oleokimia - Nadiyah, Khairun; Isfus Senjawati, Maria; Rika Putri, Gustiarini; Satria, Andika (Politeknik ATI Padang, 2025)
Improper working postures are one of the main causes of Musculoskeletal Disorders (MSDs), particularly in manual and repetitive tasks such as packaging operations. This study aims to analyze the ergonomic risks associated with workers’ postures at the packing station of an oleochemical company and to propose corrective measures to reduce potential MSDs. The assessment employed two ergonomic evaluation methods: Rapid Entire Body Assessment (REBA) to determine posture risk levels and the Nordic Body Map (NBM) questionnaire to identify body regions experiencing discomfort. The results revealed that Worker A obtained a REBA score of 8, indicating a high-risk level that requires immediate corrective action, while Worker B had a score of 3, categorized as low risk. The most frequent complaints were concentrated in the lower back, shoulders, and wrists, primarily caused by repetitive bending and lifting movements from the conveyor to the pallet. The findings suggest that the main contributing factors are improper workstation height, repetitive tasks, and prolonged standing durations. Therefore, ergonomic improvements such as adjusting the height of the conveyor and worktable, implementing scheduled microbreaks, and providing posture training are recommended. These interventions are expected to reduce the risk of MSDs, improve worker comfort, and enhance overall productivity at the packing station.